PENGARUH LEVERAGE, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN KAPASITAS OPERASI TERHADAP FINANCIAL DISTRESS - Siti Nurdian Erniza; Triana Anggraini (CV. Denasya Smart Publisher, 2025)
This study analyzes the effect of leverage, firm size, sales growth, and operating capacity on financial distress in retail companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Using quantitative descriptive methods and multiple linear regression (SPSS 22), 19 sampels from 30 companies were obtained through purposive sampling. The results show that leverage and operating capacity have a negative effect on financial distress, while firm size and sales growth have no effect.